Assessing asthma severity among children and adults with current asthma - Zahran, Hatice S. (J Asthma, 2014)
BACKGROUND: Asthma severity is a key indicator to assess asthma care and management. Severity status may vary over time. Assessing asthma severity periodically is important for monitoring the health and well-being of people with asthma. OBJECTIVE: To assess population-based asthma severity and to identify related-risk factors among children and adults with asthma. METHODS: We used the 2006–2010 BRFSS child and adult Asthma Call-back Survey. Asthma severity was classified as intermittent or persistent. We performed multivariate logistic regression to identify related-risk factors. RESULTS: Overall, 63.8% of persons with asthma had persistent asthma. Persistent asthma was more prevalent among children aged 0–4 years (71.8%; prevalence rate ratio [PR] = 1.3). Among adults with current asthma, persistent asthma was more prevalent among those who were 45 years or older (aged 45–54: 69.4%; PR = 1.1, aged 55–64: 72.6%; PR = 1.2, and aged 65+: 77.8%; PR = 1.3); annual household incomes of <$15 000 (74.1%; PR = 1.1); and first diagnosed at age 55 years or older (first diagnosed at age 55–64: 80.4%; PR = 1.1, at age 65 + : 81.5%; PR = 1.1). The prevalence of persistent asthma was also higher among current smokers who were also exposed to secondhand smoke (SHS) (74.7%; PR = 1.1); and among those with Chronic Obstructive Pulmonary Disease (COPD) (77.1%; PR = 1.2). CONCLUSIONS: Nearly two-thirds of children and adults with asthma had persistent asthma. Identifying related-risk factors could help improve targeted interventions or strategies to reduce modifiable predictors (low income, smoking, and SHS) of increased asthma severity. Such strategies could improve asthma care and quality of life.